2009
DOI: 10.1111/j.1532-5415.2008.02146.x
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness and Clinical Utility of the Geriatric Self‐Efficacy Index for Urinary Incontinence

Abstract: OBJECTIVES:To report on the responsiveness testing and clinical utility of the 12-item Geriatric SelfEfficacy Index for Urinary Incontinence (GSE-UI). DESIGN: Prospective cohort study. SETTING: Six urinary incontinence (UI) outpatient clinics in Quebec, Canada. PARTICIPANTS: Community-dwelling incontinent adults aged 65 and older. MEASUREMENTS:The abridged 12-item GSE-UI, measuring older adults' level of confidence for preventing urine loss, was administered to all new consecutive incontinent patients 1 week b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…We have shown that the tool decreased the number of daily urinary leakage episodes by about 50% and improved both self-efficacy and quality of life. The 8.7-point change in the Self Efficacy Index suggests a clinically significant improvement in incontinence-related selfefficacy [36]. This improvement in self-efficacy appears to contribute to improvement in quality of life.…”
Section: Discussionmentioning
confidence: 94%
“…We have shown that the tool decreased the number of daily urinary leakage episodes by about 50% and improved both self-efficacy and quality of life. The 8.7-point change in the Self Efficacy Index suggests a clinically significant improvement in incontinence-related selfefficacy [36]. This improvement in self-efficacy appears to contribute to improvement in quality of life.…”
Section: Discussionmentioning
confidence: 94%
“…Taking into account that among the risk factors for the development of urinary incontinence in women an important place have heredity [11,28], metabolic syndrome and overweight [24,26], age [9] it is quite understandable to study the possibility of OAB in pregnant women of different age groups depending on the characteristics of anthroposomatotypological indicators or hormonal background. W hen taken into account anthropometric and somatotypological indicators it was established that in women of different age groups, the discriminant model of the possibility of OAB occurrence covers 86.7% of pregnant women aged from 17 to 25 years, 90.9% of pregnant women aged from 26 to 35, and 89.3% of pregnant women aged from 36 to 41 years.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors consider pregnancy and childbirth to be the leading risk factors that contribute to the development of symptoms of urination [13,18,[23][24][25]28]. Statistically significant risk factors are the age of a woman, the number and quality of previous births, the weight of the newborn, as well as the body mass index [15,19,22,27].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding more about the underlying concerns of older people is essential to sensitive interactions which aim to increase self‐efficacy after hip fracture. Previous research stresses that healthcare professionals have a key role in assessing and enhancing self‐efficacy in rehabilitation contexts with older people (Tinetti et al ., ; Resnick, ; Tannenbaum et al ., ). This role is vital in enabling individuals to safely and appropriately balance risk.…”
Section: Discussionmentioning
confidence: 99%